Padlet: Learning Media Based on Collaborative Learning In AENA Course - Rusanti, Putu; Susandi, Ni Kadek Ary; Wismadewi, I Gusti Agung Galuh; Suryati, Ni Wayan Novi; Dewi, Ni Kadek Maya Cyntia; Susanta, Putu Agus Endra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Nowadays, learning media has been changed into based on information and communication technology. Padlet is an application for online learning which is similar with online board. This application can be used in learning Advance English for Nurse Anesthesiology in the classroom to encourage the students to write in online platform. The purpose of this study was to describe padlet as a learning media based on collaborative learning in AENA (Advance English for Nurse Anesthesiologist) course. This research employed descriptive research which emphasize more on explaining the data. The subject of this research was third year students of Diploma IV of Nursing Anesthesiology Data were analyzed by using descriptive qualitative. The results showed that 62% of students agreed that they enjoyed learning using Padlet media. Apart from that, there were 63% of students agreed that they were brave enough to write English using the Padlet application.